STUDI POTENSI TERIPANG DI PERAIRAN BANGKA SEBAGAI SUMBER STEROID UNTUK SEX REVERSAL IKAN NILA - ARDIANSYAH KURNIAWAN (Akuatik: Jurnal Sumberdaya Perairan, 2012)
Sea Cucumber is one of the potential of fisheries and marine Bangka Belitung. During this time, sea cucumbers used as food or processed products. In fact, sea cucumbers are known to contain active ingredients that can be used steroids for a variety of purposes. This study was conducted to determine the potential of the existing sea cucumbers in the waters of Bangka and analyze potential bioactive compounds terkadung steroids for tilapia sex reversal. Based on the results of research conducted in Cape Mount acquired a dominant species of sea cucumbers are coral sea cucumber (Holothuria nobilis), sea cucumber sap (leucospilota H.), sea cucumbers and red chest (H. edulis). After testing the qualitative potential steroid test Lieberman Burchard color visualization obtained positive results for the three types of steroids are the sea cucumbers